(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article examines the influence of social media on mental health and well-being. It discusses the potential negative effects such as comparison and self-esteem issues, fear of missing out (FOMO), cyberbullying and harassment, sleep disturbances, and social isolation. The article emphasizes the importance of maintaining a healthy balance between social media use and well-being and suggests strategies for achieving this balance. By understanding the potential pitfalls of excessive social media use, individuals can prioritize their mental health and well-being while still benefiting from virtual connections.